Metodología para seleccionar zonas de intervención con cultivos biofortificados - Monserrate Rojas, Fredy Alexander; Pachón, Helena; Hyman, Glenn G.; Vesga Varela, A.L. (FapUNIFESP, 2009)
OBJECTIVE: To identify geographical areas in Latin America and the Caribbean where biofortification of staple crops, such as beans, corn, rice, cassava, and sweet potatoes, might help reduce nutritional deficiencies in the Region.